Backcasting as a Tool for Sustainable Transport Policy Making: the Environmentally Sustainable Transport Study in the Netherlands - Geurs, Karst; van Wee, Bert (European Journal of Transport and Infrastructure Research, 2004)
This paper describes the backcasting approach used in the OECD’s Environmentally Sustainable Transport (EST) Study, in which several countries participated. The backcasting approach can be seen as an innovative tool for policy making, which aims at generating alternative images of the future. These images have been thoroughly analysed as to their feasibility, consequences and policy implications. Here, results and implications for backcasting shown in the Netherlands case study are highlighted and conclusions drawn that EST criteria will only be attainable if a substantial increase in development of technology and stringent behavioural adaptations, with changes in economic structures at an international level, are assumed. If EST is to be realised, measures will have to be taken and instruments will have to be implemented in the short term. Timely implementation will probably mean a necessary radical change in the current Dutch policy ‘life cycle’.